The role of psychiatric posting in influencing medical students, attitudes towards mental illness: A comparison between the old and new syllabus / Tan Tze Yin - Tan, Tze Yin (2017)
Medical students’ attitudes towards mental illness is of utmost importance as it may influence their view and level of care provided to their patients in the future. Medical education aims to reduce stigma associated with mental illness and create positive attitudes towards mental illness. Objective: This study aimed to assess and compare the attitudes towards mental illness among medical students under the new (third year students) and old (final year students) undergraduate syllabus before and after completion of a psychiatric clerkship. Methodology: The study design was a cross-sectional study. All participants completed self-reported questionnaires on the first and last day of their psychiatric clerkship. Participants were given a set of questionnaires which included socio-demographic details, a case vignette and two dependent measures (social distance scale and dangerousness scale) to assess their attitudes towards mental illness. Results: Pre-clerkship, a total of 226 students participated in the study (102 third year, 124 final year). Post-clerkship, a total of 197 students responded to the study (80 third year, 117 final year). There were no significant differences in the socio-demographic characteristics between the two groups of students. Both groups of students showed significantly more positive attitudes towards mental illness after completion of clerkship (third year: SDS – p<0.024, DS – p<0.001; final year: SDS – p<0.007, DS – p<0.001). Students under the new undergraduate syllabus showed significantly less stigmatizing attitudes compared with students under the old syllabus even prior to starting their psychiatry clerkship (SDS – p<0.007, DS – p<0.001). viii Conclusion: Psychiatric clerkship have shown to improve attitudes towards mental illness among the medical students. The new undergraduate syllabus brought about a more positive attitudinal change compared with the old syllabus.